Promising emission behavior in Pr 3+ /In selenide-chalcogenide-glass small-core step index fiber (SIF) - Sakr, Hesham; Tang, Zhuoqi; Furniss, David; Sojka, Lukasz; Sujecki, S.; Benson, Trevor M.; Seddon, Angela B. (Elsevier, 2017)
Selenide-chalcogenide glass, small-core, step-index fiber (SIF), core-doped with Pr3+: 9.51 × 1024 ions m−3 (500 ppmw) is fabricated for the first time with indium to help solubilize Pr3+. Core diameters of 20 or 40 μm are confirmed using scanning electron microscopy and near-field imaging; fibre numerical aperture is ∼0.4. Optical loss is ≥ 4.9 dB m−1 across the 3–9 μm mid-infrared (MIR) spectral range. On pumping at 1.55 μm or 2.013 μm, the SIFs give broad MIR emission across 3.5–6 μm assigned to 3H6 → 3H5 and 3H5 → 3H4. The Pr3+ emission-lifetime at 4.7 μm decreases from bulk-glass (10.1 ± 0.3 ms), to intermediately processed fiber (8.10 ± 0.5 ms) to SIF (7.1 ± 0.5 ms) induced by the processing. On end-pumping SIFs at 2.013 μm, the output pump-power and emission intensity at 4.7 μm became sub-linear and super-linear, respectively, suggesting MIR excited-state saturation is occurring.